2018
DOI: 10.1016/j.jinteco.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Does economic structure determine financial structure?

Abstract: In this paper, we examine the relationship between the structure of the real economy and a country's financial system. We consider whether the development of the real economic structure can predict the direction of evolution of a country's financial structure. Using data for 108 countries, we find a significant relationship between real economic structure and financial structure. Next, we exploit shocks to the economies in India, Finland and Sweden, and South Korea and show that changes in the economic structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 75 publications
(81 reference statements)
2
22
0
Order By: Relevance
“…First, the variable GDP per capita has a positive and significant coefficient through all the specifications. This result confirms empirical studies that have demonstrated a positive relationship between the level of economic development and the structure of the financial system (Allen et al, 2007; Ergungor 2004; Kwok & Tadesse, 2006). It also corroborates the argument that the more the GDP per capita increases, the more economic agents will seek sophisticated services.…”
Section: The Role Of Democracy In Explaining the Structure Of The Financial System: An Empirical Assessmentsupporting
confidence: 89%
See 3 more Smart Citations
“…First, the variable GDP per capita has a positive and significant coefficient through all the specifications. This result confirms empirical studies that have demonstrated a positive relationship between the level of economic development and the structure of the financial system (Allen et al, 2007; Ergungor 2004; Kwok & Tadesse, 2006). It also corroborates the argument that the more the GDP per capita increases, the more economic agents will seek sophisticated services.…”
Section: The Role Of Democracy In Explaining the Structure Of The Financial System: An Empirical Assessmentsupporting
confidence: 89%
“…Following Ergungor (2004) and Allen et al (2007), we retain two variables to measure the structure of the financial system. The first variable measures the size of the financial structure, while the second measures its activity.…”
Section: The Role Of Democracy In Explaining the Structure Of The Financial System: An Empirical Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Capital could come from own capital or loan capital or debt. Therefore, determining an optimal capital structure is also important, especially for go public companies in the capital market (Black & Gilson, 1988;Alti, 2006;Ang et al, 2018;Allen et al, 2018;Roychowdhury & Srinivasan, 2019).…”
mentioning
confidence: 99%